L'espiritualitat de sant Vicent Ferrer en el context de la seua època. - NAVARRO SORNÍ, MIGUEL (Scripta, 2019)
The aim of this article is to analyze the spirituality of Saint Vicent Ferrer within the crisis context of his time, and to show how this context influenced most properties of his spirituality; particulary, as his most relevant characteristic, his evangelic preaching, which summarizes his life and doctrine.